Studi Lapangan SSOP (Sanitation Standard Operating Procedure) UKM Kripik Tempe “Mulyo Sari” - Latifasari, Nurul; Dewi, Fitranaya Arlian Cintaya; Awaludin, Muhammad Tata; Wulandari, Devi; Salsa Bilah, Al Haya Nurjanah Afifah; Septiani, Fauziah Bunga; Kurniawan, Rizky (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2025)
Small and medium businesses are businesses managed on an individual scale or as an individual business entity. Even though it is small-scale, business actors must still pay attention to hygiene aspects from the start of production until the product reaches the hands of consumers, as stated in Law No. 18 of 2012 concerning Article 70, which states that food sanitation is carried out so that food is safe for consumption. The production of "Mulyo Sari" tempeh chips is one of the small and medium businesses located in Purwokerto, Banyumas Regency, which will be used as an object of community service that aims to provide solutions based on academic studies regarding Sanitation Standard Operating Procedures. The methods used include observation, interviews, and providing solutions. The results of the field study showed that there were several weaknesses in the implementation of the Sanitation Standard Operating Procedure, such as a lack of personal protective equipment by employees, no separation of areas, the location of water containers near waste dumps, and a lack of waste processing. So that Sanitation Standard Operating Procedures are improved by providing solutions that are expected to improve product quality, food safety, and environmental sustainability.